AQUAPONIC PIPING SYSTEM DESIGN CLOSED CIRCULATION WITH HEAD LOSS ANALYSIS AND PUMP PERFORMANCE - Melyani Melyani; Desmarita Leni; Muchlisinalahuddin Muchlisinalahuddin; Yuni Vadila; Acep Wagiman (International Journal of Multidisciplinary Research and Literature, 2026)
Closed circulation aquaponic systems require proper piping design and pump selection to ensure flow stability, energy efficiency, and operational sustainability. This study aims to design and experimentally validate an aquaponic piping system based on major and minor head loss analysis and determination of Total Dynamic Head (TDH) as the basis for pump selection. The methods used include theoretical calculations using the Darcy Weisbach Equation, system curve construction (HQ), and experimental testing through measurements of actual discharge, pressure, and pump electrical power under real operating conditions. The results show that minor head loss dominates the total energy loss (±66%), while major head loss contributes ±34%. The system TDH is obtained at ±2.2-2.4 m at a design discharge of 24 L/min. Experimental testing shows an actual discharge of 22–23 L/min with a deviation of <8% from the theoretical calculation. Actual pump power shows operational efficiency in the range of 48–55%. Pipe diameter sensitivity analysis shows that increasing the main diameter by 1 level can reduce head loss by 18–25% and reduce pump power requirements by ±12%. These results confirm that optimizing fitting layout and diameter selection has a greater impact on system efficiency than simply increasing pump capacity. This research contributes a system curve-based design approach and experimental validation to improve the reliability and energy efficiency of closed-circulation aquaponics systems.